The Concept of Human Rights in the Maqasid al-Shariah Perspective - Rambe, Toguan; Nasution, Kasron; Matondang, Siti Khodijah (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2026)
This study examines the conceptual dichotomy that often arises between universal Human Rights (HAM) and the fundamental goal framework of Islamic law, namely Maqasid Sharia. There is an urgency to harmonize these two concepts in order to strengthen the guarantee of humanitarian protection in the legal system. This study uses a literature study method with a descriptive research nature with a comparative approach, examining primary and secondary legal materials, as well as Islamic legal doctrine. The main objective of this study is to analyze the convergence and substantial coherence between human rights principles and the five essential objectives of Maqasid Syari